Implementation of the Hybrid Contract Concept in Multiservice Ijarah Financing as a Financing Alternative Health Service in the Covid-19 Pandemic - Darti Busni; Doli Witro; Iwan Setiawan; Nana Herdiana Abdurrahman; Raid Alghani (Institut Agama Islam Negeri Batusangkar, 2022)
This article discusses applying the hybrid contract concept in multiservice ijarah financing as an alternative to financing health services. This is important to study because health services are one of the most urgent things in the current Covid-19 pandemic. This article aims to determine the form of contracts contained in multiservice ijarah financing as an alternative to financing health services in the Covid-19 pandemic. This type of research is normative legal research. The data were obtained from library materials such as books, journals, etc. The analysis results show that health financing can be carried out in two ways: the ijarah contract, which begins with the bank through investors doing the health institution after making the contract, and the wakalah contract through the customer himself. People who have financial problems paying for health costs with multiservice ijarah transactions can apply for health financing to Islamic Financial Institutions for their families to minimize deaths before treatment in the Covid-19 pandemic.